A new family of NaTMGe (TM = 3d transition metals) half-Heusler compounds: the role of TM modification. Issue 40 (16th September 2022) - Vu, Tuan V.; Nguyen, Duy Khanh; Guerrero-Sanchez, J.; Rivas-Silva, J. F.; Cocoletzi, Gregorio H.; Hoat, D. M.
Abstract : Band structures of NaTMGe half-Heusler compounds. Abstract : Exploring Heusler based materials for different practical applications has drawn more and more attention. In this work, the structural, electronic, magnetic, and mechanical properties of NaTMGe (TM = all 3d transition metals) half-Heusler compounds have been systematically investigated using first-principles calculations. The TM modification plays a determinant role in the fundamental properties. Except NaNiGe and NaCuGe, the studied materials exhibit good dynamical stability. Calculations reveal the non-magnetic semiconductor of NaScGe with a direct energy gap of 1.21 eV. Prospective spintronic applications of NaVGe and NaCrGe–NaMnGe are also suggested by their magnetic semiconductor and half-metallic behavior, respectively, where their magnetic properties follow the Slater–Pauling rule. Nevertheless, the remaining materials are either magnetic or non-magnetic metallic. For the magnetic systems, the magnetism is induced mainly by the TM constituents with either spin-up (V, Cr, Mn, and Fe) or spin-down (Co) 3d states. Calculated elastic constants indicate that all compounds are mechanically stable. Furthermore, they exhibit significant elastic anisotropy, where NaScGe and NaZnGe are the least and most anisotropic materials, respectively. Also, modifying the TM elements influences the materials' ductile and brittle behaviors. Our work unravels clearly the effects of TM modification on the fundamental properties of NaTMGe compounds. NaTMGe materials show excellent versatility with promising properties for optoelectronic and spintronic applications.